Association between learning engagement and learning satisfaction among first-year business students in higher education: the moderating effect of gender - Edmond Kwesi Agormedah (Discover Education)
Abstract Many university students, including first-year business education students (FYBES) in Ghana, struggle to adjust to academic demands and university life, leading to low engagement and satisfaction with academic experiences. Despite efforts to improve student engagement and satisfaction, the extent to which gender influence this relationship remains unclear, particularly in the context of FYBES in Ghana. This inquiry aims to examine the influence of learning engagement (LE) on learning satisfaction (LS) among FYBES, with a specific focus on the moderating role of gender. Using explanatory correlational research design, data was gathered with questionnaire from 165 FYBES from a higher education in Ghana using the census method. The measurement and structural models were examined using PLS-SEM. The moderation analysis was performed using Hayes PROCESS Macro with 10,000 bootstrap samples. The study discovered that FYBES were highly satisfied with their academic experiences and experienced a high level of LE. However, gender does not influence LS and LE among students. Further, LE has a significant positive effect on LS among students, however, this relationship is direct and not dependent on gender. With the same level of LE, female students, relative to males, are more likely to exhibit higher levels of LS. Business educators and administrators should continue to prioritise interventions and strategies to promote engagement and satisfaction in the classroom. These interventions and strategies should be gender-neutral approach.